Beispiel Nr: 17
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 1 x +3 + -2 z=3\\ 3 x +2 y + 1 z=2\\ 0 x +1 y + 3 z=5\\ \\ \\ \textbf{Rechnung:} \\ 1 x + 3 y + -2 z=3\\ 3 x +2 y +1 z=2\\ 0 x +1 y +3 z=5\\ D_h=\left|\begin{array}{ccc} 1\ & 3 & -2\\ 3&2 & 1\\ 0& 1 & 3 \\ \end{array}\right| \begin{array}{cc} 1\ & 3 \\ 3&2 \\ 0& 1 \end{array} \\ D_h=1 \cdot 2 \cdot 3+3 \cdot 1 \cdot 0 +\left(-2\right) \cdot 3 \cdot 1 - \left(-2\right) \cdot 2 \cdot 0 -1 \cdot 1 \cdot 1 -3 \cdot 3 \cdot 3=-28 \\ D_x=\left|\begin{array}{ccc} 3\ & 3 & -2\\ 2&2 & 1\\ 5& 1 & 3 \\ \end{array}\right| \begin{array}{cc} 3\ & 3 \\ 2&2 \\ 5& 1 \end{array} \\ D_x=3 \cdot 2 \cdot 3+ 3 \cdot 1 \cdot 5 +\left(-2\right) \cdot 2 \cdot 1 - \left(-2\right) \cdot 2 \cdot 5 - 3 \cdot 1 \cdot 1 -3 \cdot 2 \cdot 3=28\\ D_y=\left|\begin{array}{ccc} 1\ & 3 & -2\\ 3&2 & 1\\ 0& 5 & 3 \\ \end{array}\right| \begin{array}{cc} 1\ & 3 \\ 3&2 \\ 0& 5 \end{array} \\ D_y=1 \cdot 2 \cdot 3+3 \cdot 1 \cdot 0 +\left(-2\right) \cdot 3 \cdot 5 - \left(-2\right) \cdot 2 \cdot 0 -1 \cdot 1 \cdot 5 -3 \cdot 3 \cdot 3=-56 \\ D_z=\left|\begin{array}{ccc} 1\ & 3 & 3\\ 3&2 & 2\\ 0& 1 & 5 \\ \end{array}\right| \begin{array}{cc} 1\ & 3 \\ 3&2 \\ 0& 1 \end{array} \\ D_z=1 \cdot 2 \cdot 5+3 \cdot 2 \cdot 0 +3 \cdot 3 \cdot 1 - 3 \cdot 2 \cdot 0 -1 \cdot 2 \cdot 1 -3 \cdot 3 \cdot 5=-28\\ x=\frac{28}{-28} \\ x=-1 \\ y=\frac{-56}{-28} \\ y=2 \\ z=\frac{-28}{-28} \\ z=1\\ L=\{-1/2/1\} $